Resource efficiency and environmental impact of juglone in Pericarpium Juglandis: A review - Liu, Shuoguo; Cheng, Sijing; Jia, Jinping; Cui, Jiahua (Frontiers in Environmental Science, 2022)
Black walnut (Juglans nigra) is considered one of the most valuable plants, with a global production of 3.5 million tons of dried fruit yearly. Throughout the past two millennia, its allelopathic effects have been widely recognized. Black walnuts produce a natural naphthoquinone called juglone, which occurs naturally in all parts of the tree, particularly the green husk, and contributes significantly to the allelopathic effects of black walnut. Except for the fruit’s edible nature, the walnut green husk has been used for centuries to make wine, natural dyes, and traditional medicines to cure certain diseases. Within the extracts of walnut green husk, 1,4-naphthoquinones, gallic acid, caffeic acid, and quercitrin were separated and characterized. Among these compounds, the major active ingredient with a good application prospect is juglone, which has proven to be a natural chemical compound with anticancer, antitumor, antibacterial, and antiviral activities, especially the strong anticancer activity. Juglone is also an environmentally friendly biological pesticide and herbicide. Certainly, the environmental impact of juglone also needs to be considered. Significant quantities of walnut green husk are currently produced as a byproduct of walnut production; however, its value has not been fully utilized and explored, which raises environmental concerns. This review attempts to: 1) summarize the origin and historical use of walnut and walnut green husk; 2) introduce the structure, biosynthesis pathway, extraction method, biological activity, and potential applications of juglone, as well as its environmental impact assessment.